Uma análise do discurso quadrinístico: práticas institucionais e interdiscurso - Lucas Piter Alves Costa (2016)
Since Comics began to become subject of studies, it has been common efforts to define them by some researchers, theoreticians and practitioners. The understanding of the Comics is closely related to the understanding of its origin, its historical background, of the usages and its language applications, as well as changes and, above all, diversification of these aspects. The history of Comics, then, takes on different features depending on the valued aspects. As products with greatly heterogeneous nature, genres of Comics set in motion a whole system of institutional practices that, in turn, may also be associated with the Arts and Media. Independently of the origin and the adopted definition, the status of Comics reveals that this cultural niche has undergone numerous changes, coming to consolidate itself as relatively autonomous area in the cultural panorama. The Comics language, their themes developed, their forms of production, circulation and reception has been improved. As discursive institution, the Comics have their own social and discursive practices and tends to share others practices with several institutions. Facing these observations, the aims of this work are: (a) to describe some language practices of the comics field; (b) to verify the functioning of the Authors name in the discursive institution of Comics; (c) to analyze the constitution of the Authors name in the discourse of Comics. The route of analysis and theoretical elaboration of this study sought to describe the Comic fields structure and the social and discursive practices that enabled the institution of the Comics as relatively autonomous domain. This study sought to make a distinction between the Author taken as subject in the discourse and the Author taken as enunciated, that is, as a product of this same discourse. In order to do this, several authorship schemas of the Comics Discourse were described and analyzed. The analysis of Comics led us to conclude that the Author's name is a type of complex enunciated supported collectively by all the discursive institution.